POSTMODERNISME, BUDAYA MASSA DAN MUSIK IBADAH MASA KINI - Sema, Daniel (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
Postmodernism is a reaction against modernism that emerged since the 19th century. In postmodernism, the mind is replaced by desire, reason is replaced by emotion, and morality is replaced by relativism. Reality is nothing more than a social construction; truth is equated with strength or power. Self identity arises from the group. Postmodernism has a characteristic of fragmentation, indeterminacy, and distrust of all things universal (world of view). One of the effects of postmodernism is the rise of mass culture and the spirit of consumerism that has spread everywhere, including church and liturgical music. This phenomenon certainly deserves to be addressed wisely so that the church stays on the right track.